Learning Induces Transient Upregulation of Brevican in the Auditory Cortex during Consolidation of Long-Term Memories - Niekisch, Hartmut; Steinhardt, Julia; Berghaeuser, Julia; Bertazzoni, Sara; Kaschinski, Erika; Kasper, Jana; Kisse, Martin; Mitloehner, Jessica; Singh, Jeet B.; Weber, Judith; Frischknecht, Renato; Happel, Max F. K. (Journal of Neuroscience, 2019)
It is a daily challenge for our brains to establish new memories via learning while providing stable storage of remote memories. In the adult vertebrate brain, bimodal regulation of the extracellular matrix (ECM) may regulate the delicate balance of learning-dependent plasticity and stable memory formation. Here, we trained adult male mice in a cortex-dependent auditory discrimination task and measured the abundance of ECM proteins brevican (BCN) and tenascin-R over the course of acquisition learning, consolidation, and long-term recall in two learning-relevant brain regions; the auditory cortex and hippocampus. Although early training led to a general downregulation of total ECM proteins, successful retrieval correlated with a region-specific and transient upregulation of BCN levels in the auditory cortex. No other parameter such as arousal or stress could account for the transient and region-specific BCN upregulation. This performance-dependent biphasic regulation of the ECM may assist transient plasticity to facilitate initial learning and subsequently promote the long-term consolidation of memory.
CRIS-Team WoS Importer:2019-09-20